2015
DOI: 10.7717/peerj.1385
|View full text |Cite
|
Sign up to set email alerts
|

Variation in species diversity and functional traits of sponge communities near human populations in Bocas del Toro, Panama

Abstract: Recent studies have renewed interest in sponge ecology by emphasizing the functional importance of sponges in a broad array of ecosystem services. Many critically important habitats occupied by sponges face chronic stressors that might lead to alterations in their diversity, relatedness, and functional attributes. We addressed whether proximity to human activity might be a significant factor in structuring sponge community composition, as well as potential functional roles, by monitoring sponge diversity and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 71 publications
(96 reference statements)
2
14
1
Order By: Relevance
“…in the perturbed zones. Similar decrease in species richness (S) and Shannon diversity index (H′) due to anthropogenic impacts has been previously reported for the coral communities in the study area (Tkachenko et al, 2016) and for sponge diversity in different oceans (Powell et al, 2014; Easson et al, 2015). Indeed, low diversity but high abundance with dominance of a few species is a common feature of many polluted habitats (Piola and Johnston, 2008; Powell et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…in the perturbed zones. Similar decrease in species richness (S) and Shannon diversity index (H′) due to anthropogenic impacts has been previously reported for the coral communities in the study area (Tkachenko et al, 2016) and for sponge diversity in different oceans (Powell et al, 2014; Easson et al, 2015). Indeed, low diversity but high abundance with dominance of a few species is a common feature of many polluted habitats (Piola and Johnston, 2008; Powell et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Sponges usually show a high species diversity in well-preserved ecosystems (Van Soest et al, 2012), which has been suggested to decrease under anthropogenic pressures (Easson et al, 2015). Shifts in nutrient cycling and ecosystem functioning, which occur in degraded reef systems (Bell et al, 2013, 2018; Easson et al, 2015), are considered to be responsible for decreases in sponge biodiversity. However, a few, likely opportunistic, sponge species have been reported to inhabit and even dominate degraded coral reefs (Maliao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Because other factors (broadly co‐varying with latitude) may influence cryptobenthic fish assemblages (e.g., population density, shipping traffic), we insured that docks within each location were spread across a variety of sites with varying abiotic factors. For example, docks in Panama ranged from Bocas town to the relatively pristine Punta Caracol (Easson, Matterson, Freeman, Archer, & Thacker, ), while docks in Belize were spread across inshore and outer‐shelf sites of the Belizean Barrier Reef, and docks in North Carolina ranged from the City pier of Beaufort to the Shackleford Banks (Fig. ).…”
Section: Methodsmentioning
confidence: 99%
“…Our dataset increases the knowledge of southwest Puerto Rico's altiphotic and mesophotic fish, coral, and sponge assemblages. We highlight the need to continue monitoring this dynamic ecosystem and emphasize that it is crucial to perform long-term time series assessments of the general area to fully assess any fluctuations in community structure (i.e., abundance, dominant species shift, disease, bleaching) (Wulff, 2001(Wulff, , 2006Easson et al, 2015) and preservation of the overall marine biodiversity (Miloslavich et al, 2010;Jenkins and van Houtan, 2016;Hoeksema et al, 2017). This study demonstrates that altiphotic and mesophotic reefs across the Guánica continental shelf edge support different assemblages of corals, sponges and fish.…”
Section: Resultsmentioning
confidence: 86%